2022
DOI: 10.3389/fnagi.2022.998292
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet prevents chronic sleep deprivation-induced Alzheimer’s disease by inhibiting iron dyshomeostasis and promoting repair via Sirt1/Nrf2 pathway

Abstract: Sleep deprivation (SD) is one of the main risk factors for Alzheimer’s disease (AD), but the underlying mechanism is still unclear. Ketogenic diet (KD) has been shown widely neuroprotective effects but less known about its effect on SD-induced AD. In the present study, a continuous 21 days SD mouse model with or without KD was established. The changes of cognitive function, pathological hallmarks of AD, ferroptosis, and intracellular signal pathways in mice were detected by Morris water maze, ThS staining, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…Compared with normal people, the phenomenon of brain iron deposition is more evident in AD patients with increasing age. This further demonstrates that the phenomenon of iron deposition is inseparable from the development process of the CNS diseases [4]. Microglia are the main cells that accumulate iron ions in neurodegenerative diseases.…”
Section: Alleviation Of Iron Homeostasis Disordersmentioning
confidence: 70%
See 2 more Smart Citations
“…Compared with normal people, the phenomenon of brain iron deposition is more evident in AD patients with increasing age. This further demonstrates that the phenomenon of iron deposition is inseparable from the development process of the CNS diseases [4]. Microglia are the main cells that accumulate iron ions in neurodegenerative diseases.…”
Section: Alleviation Of Iron Homeostasis Disordersmentioning
confidence: 70%
“…tau protein Abnormal phosphorylation, leading to cognitive impairment, further promotes the development of AD. If the aggregation of Aβ is reduced or prevented, the development of Alzheimer's disease can be prevented or even prevented [4]. Several investigations have discovered that AD can stop the development of AD by preventing cognitive decline, amyloid buildup, and tau hyperphosphorylation brought on by persistent SD.…”
Section: Effects Of Ketogenic Diet On Alzheimer's Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 53 ] Other studies showed that suppressing hippocampal ferroptosis could alleviate SD‐induced memory loss. [ 13,54 ] In summary, these findings indicate that the Sirt1/Nrf2/HO‐1/Gpx4 signaling pathway is a potential therapeutic target for SD‐induced cognitive impairment.…”
Section: Discussionmentioning
confidence: 85%
“…Although ketogenic diets might seem like a social media fad, emerging science explores their role in various health conditions, including obesity, neurologic, psychiatric and sleep disorders. [5][6][7] The low-carbohydrate, high-fat diet appears to confer a neuroprotective effect; however, the mechanisms of action remain under investigation.…”
mentioning
confidence: 99%